Burnout and depression in high level young athletes - Beckmann, J.; Nixdorf, I.; Frank, R. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Previous research has shown high levels of chronic stress, coping strategies, and the balance of physical and psychological stress and recovery to influence the development of burnout and depression in elite athletes (Nixdorf et al., 2013). High level young athletes seem to be especially vulnerable to theses factors. To deal with this problem a burnout and depression screening instrument for young athletes was developed based on the findings from 3 studies. Methods: In a cross-sectional study (Nixdorf et al., submitted), questionnaires on Team Cohesion, Perfectionism in Sport, Sport Attributional Style, and Depression were administered to German junior elite athletes (N = 199; M age = 14.96; SD = 1.56). The data was analyzed by a mediator analysis using path analysis with bootstrapping. In a longitudinal study with 3 repeated measures (N=246; M age=15.22; SD=1.99), in addition to depression athlete burnout was assessed along with experienced stress and recovery. A qualitative study further explored major stressors in elite athletes (Nixdorf et al,, 2015). Results: In all 3 studies athletes in individual sports showed significant higher scores in depression than athletes in team sports. In the cross-sectional study attribution after failure accounted for a mediation with a significant indirect effect ( = .07; p < .05) and significant coefficients with sport discipline ( = .27; p < .001) and to the dependent variable depression ( = .26; p < .01). Whereas cohesion showed a significant negative relationship to depression, perfectionism was positively related to depression. In the longitudinal study a medium correlation between burnout and depression was found (r = .52, p < .001). The qualitative study detected three main sources of stress: double burden, sport specific demands and conditions. Discussion: All 3 studies furnished concurrent findings on sport specific mechanisms contributing to depressive syndromes and burnout in high level young athletes. The assessment instruments used in the longitudinal study proved to be relevant for an early assessment of burnout and depression symptoms. They were included in a screening instrument that is further tested.